The Genes Associated with Drought Tolerance by Multi-Layer Approach in Potato - Kim, Chang-Kug; Oh, Jae-Hyeon; Cho, Chuloh; Kim, Kyung-Hwa; Yu, Go Eun; Kim, Dool-Yi (Plant breeding and biotechnology, 2019)
We have developed a multi-layer pipeline that uses transcriptomic data to identify candidate genes associated withcomplex pathways in plants. We used this multi-layer approach, incorporating microarray, RNA sequencing, polymerase chain reaction(PCR), and protein-protein interaction analyses, to identify 14 genes associated with drought tolerance in potato. We generatedtransgenic potato lines that over-express bZIP28, one of the genes selected by our pipeline, to confirm the involvement of that gene indrought tolerance. The protein interactions of the products of the screened genes were assessed using yeast two-hybrid and bimolecularfluorescence complementation analyses. Overall, this study demonstrated the utility of our multi-layer approach for decipheringcomplex biosynthetic pathways using transcriptomic data. KCI Citation Count: 0